1974
DOI: 10.1002/1097-4679(197407)30:3<358::aid-jclp2270300341>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

First prison admissions with juvenile histories and absolute first offenders: Frequencies and MMPI profiles

Abstract: PROBLEMThis paper considers two questions: (1) of the men who are serving their first prison sentences (first "termers"), what proportion have prior histories as adjudicated juvenile offenders; and (2) of the first "termers," how do the AlAlPI profiles of those with prior histories as adjudicated juvenile offenders compare to the AMPI profiles of absolute first offenders (first adjudicated offense). There is a main study and a short replication study.Sutherland and Cressey(6* p . 272) question the popular assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1975
1975
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…(He did not select a cutoff score, however.) Adams (1976;2) also reexamined the HC scale and found that it effectively differentiated recidivists from first offenders, as did its parent scales Pd and A p. Flanagan and Lewis (1974;2) found that offenders with juvenile records scored significantly higher than "absolute first offenders" on the F, Pd, Pa, Sc, and Ma scales and significantly lower on the Responsibility (Re) scale. Christensen and LelJnes (1974;1) used the Prison Adjustment Scale (PAS) in addition to the conventional scales, but they failed to achieve any significant differentiations with respect to recidivism.…”
Section: The Mmpi As a Primary Differentiator Oj Deviant Behaviormentioning
confidence: 99%
“…(He did not select a cutoff score, however.) Adams (1976;2) also reexamined the HC scale and found that it effectively differentiated recidivists from first offenders, as did its parent scales Pd and A p. Flanagan and Lewis (1974;2) found that offenders with juvenile records scored significantly higher than "absolute first offenders" on the F, Pd, Pa, Sc, and Ma scales and significantly lower on the Responsibility (Re) scale. Christensen and LelJnes (1974;1) used the Prison Adjustment Scale (PAS) in addition to the conventional scales, but they failed to achieve any significant differentiations with respect to recidivism.…”
Section: The Mmpi As a Primary Differentiator Oj Deviant Behaviormentioning
confidence: 99%
“…Concomitantly, numerous studies have been clonducted in which there has been an attempt to identify associaltions between personality patterns and criminological variables. Especially frequent have been efforts to differentiate among offenders who have been classified according to the type or seriousness of their most recent antisocial behavior (Blackburn, 1968 ;Ruck & Graham, 1978;Carroll & Fuller, 1971;Davis C Sines, 1971;Deiker, 1974;Holland & Holt, 1975 ;McCreary, 1976 ;Megargee & Meindelsohn, 1962;Panton, 1958;Persons & Narks, 1971;Rader, 1977), although studies of first offenders versus recidivists (Bauer & Clark, 1976;Christensen & LeUnes, 1974;Clark, 1948;Dunhxm, 1954;Flanagan & Lewis, 1974;Panton, 1959Panton, , 1962a and probationparole violators versus nonviolators (Gough, Wenk, & Rozynko, 1965;Jacobson & Wirt, 1969;Mack, 1969;Mandel & Barron, 1966;Panton, 1962b ;Smith & Lanyon, 1968) have also often been reported.…”
Section: Multivariate Behavioralmentioning
confidence: 77%
“…Correctional research that has employed the MMPI (Hathaway & McKinley, 1967) has focused on the clinical Psychopathic Deviate scale (PD), either alone or in combination with several other MMPI scales. Often, its application has been to assess criminal offenders with respect to hostile and aggressive behavior (Davis & Sines, 1971;Holland, Beckett, & Levi, 1981), management problems (Panton, 1973), and recidivism (Adams, 1976;Flanagan & Lewis, 1974).…”
mentioning
confidence: 99%